Interferon-induced RIP1/RIP3-mediated necrosis requires PKR and is licensed by FADD and caspases - Thapa, Roshan J. (National Academy of Sciences, 2013)
Interferons (IFNs) are cytokines with powerful immunomodulatory and antiviral properties, but less is known about how they induce cell death. Here, we show that both type I (α/β) and type II (γ) IFNs induce precipitous receptor-interacting protein (RIP)1/RIP3 kinase-mediated necrosis when the adaptor protein Fas-associated death domain (FADD) is lost or disabled by phosphorylation, or when caspases (e.g., caspase 8) are inactivated. IFN-induced necrosis proceeds via progressive assembly of a RIP1–RIP3 “necrosome” complex that requires Jak1/STAT1-dependent transcription, but does not need the kinase activity of RIP1. Instead, IFNs transcriptionally activate the RNA-responsive protein kinase PKR, which then interacts with RIP1 to initiate necrosome formation and trigger necrosis. Although IFNs are powerful activators of necrosis when FADD is absent, these cytokines are likely not the dominant inducers of RIP kinase-driven embryonic lethality in FADD-deficient mice. We also identify phosphorylation on serine 191 as a mechanism that disables FADD and collaborates with caspase inactivation to allow IFN-activated necrosis. Collectively, these findings outline a mechanism of IFN-induced RIP kinase-dependent necrotic cell death and identify FADD and caspases as negative regulators of this process.